Effect of eight-week high-intensity interval training versus moderate-intensity continuous training programme on body composition, cardiometabolic risk factors in sedentary adolescents - Sun, Fucheng; Williams, Craig A.; Sun, Qiang; Hu, Feng; Zhang, Ting (Frontiers in Physiology, 2024)
Objectives: This study aimed to assess and compare the effect of an eight-week highintensity interval training (HIIT) or moderate-intensity continuous training (MICT) programme on body composition and cardiovascular metabolic outcomes of sedentary asymptomatic adolescents in China.Methods: Eighteen sedentary normal-weightasymptomatic adolescents (age: 18.5±0.3 years, 11 females) were randomized into three groups. HIIT group protocol consisted of three sessions/week for eight-week of "all out" sprints to reach 85-95% of HRmax, and MICT group protocol undertook three sessions/week for eight-week of continuous running to reach 65-75% of HRmax. The control group resumed normal daily activities without any intervention. Blood pressure and body composition were measured, and fasting blood samples were obtained at baseline and 48h post-trial. Mixed-design ANOVA analysis was employed followed by post-hoc t-tests and Bonferroni alpha-correction was used to evaluate interaction, between-group, and within-group differences, respectively.Results: Results indicated that HIIT and MICT similarly affected body fat mass (p=0.021, ES=0.19; p=0.016, ES=0.30, respectively), body fat percentage (p=0.037, ES=0.17; p=0.041, ES=0.28, respectively), visceral fat area (p=0.001, ES=0.35; p=0.003, ES=0.49, respectively) of body composition. A positive outcome was observed for waist/hip ratio (p=0.033, ES=0.43) in HIIT, but not MICT (p=0.163, ES=0.33). No significant differences were found between groups for any clinical biomarkers. However, pairwise comparison within the group showed a significant decrease in systolic blood pressure (p=0.018, ES=0.84), diastolic blood pressure (p=0.008, ES=1.76), and triglyceride (p=0.004, ES=1.33) in HIIT, but no significant differences were found in the MICT and Control group.: Both eight-week HIIT and MICT programmes have similar positive effects on reducing body fat mass, fat percentage, and visceral fat area. However, Sedentary sedentaryasymptomatic adolescents may have limited scope to decrease insulin resistance after these an eight-week interventions. Notably, HIIT and MICT, but an the eight-week HIIT intervention was highly effective in increasing cardiometabolic health compared to the MICT. The exercise intensity threshold value and metabolic outcomes of highintensity interval sprints should be explored further to extend the long-term benefit in this cohort.